50 American heroes every kid should meet! - Denenberg, Dennis, 1947-; Roscoe, Lorraine, 1955- (Brookfield, Conn. : Millbrook, 2001)
Contains profiles of fifty American men and women from the past and present who have made exceptional, positive contributions to the world, including artists, activists, aviators, scientists, teachers, musicians, inventors, athletes, journalists, jurists, and others.
Includes bibliographical references and index.
6.8
3-6
Keywords: Heroes -- United States -- Biography -- Juvenile literature; United States -- Biography -- Juvenile literature; Heroes -- United States; United States; Heroes and heroines -- Biography; United States -- Biography